Dietary supplementation with Clostridium autoethanogenum protein improves growth performance and promotes muscle protein synthesis by activating the mTOR signaling pathway of the broiler - Shan, Chunqiao; Liu, Yan; Ma, Chaoxin; Li, Chuang; Liu, Qiuchen; Liu, Sisi; Jiang, Guotuo; Tian, Jing (Frontiers in Veterinary Science, 2024)
The experiment aimed to evaluate the effects of different ratios of Clostridium autoethanogenum protein (CAP) used in the diets on the growth performance, muscle quality, serum indexes, and mTOR pathway of white feather broilers. Four hundred and eighty 1-day-old Arbor Acres (AA) broilers, comprising equal numbers of males and females, were randomly assigned to one of four treatments, and each treatment consisted of 12 replicates of 10 birds. Four diets were formulated based on isoenergetic and isonitrogenous principles. The control group (CAP 0) did not receive any CAP, while the experimental groups received 2% (CAP 2), 3% (CAP 3), and 4% (CAP 4) of CAP for six weeks. Compared with the CAP0, (1) The feed conversion ratio (FCR) was lower (P < 0.05), and the leg muscle yield was higher (P < 0.05) in the CAP3 and CAP4; (2) The serum levels of TP, ALB, T-AOC, and SOD were improved in the CAP3 (P <0.05); (3) The expression of Lipin-1 gene was downregulated and AMPKɑ2, Akt, and 4E-BP1 genes were up-regulated in the experiment group (P < 0.05); (4) The inclusion of 3% CAP in the diet increased the levels of 4E-BP1, S6K1, Akt, and AMPKɑ2 phosphorylation by modulating the mTOR signaling pathway (P < 0.05). In conclusion, broiler diets containing 3% CAP can activate the mTOR signaling pathway to promote muscle synthesis and improve growth performance.